Prognostic and diagnostic implications of epithelial cell adhesion/activating molecule (EpCAM) expression in renal tumours: a retrospective clinicopathological study of 948 cases using tissue microarrays. (15th January 2014) - Zimpfer, Annette; Maruschke, Matthias; Rehn, Stefan; Kundt, Guenter; Litzenberger, Anke; Dammert, Friederike; Zettl, Heike; Stephan, Carsten; Hakenberg, Oliver W.; Erbersdobler, Andreas
<x xml:space="preserve">Abstract</x> Objective To evaluate the expression and prognostic value of epithelial cell adhesion/activating molecule (EpCAM) in a large set of renal cell carcinomas (RCCs) using a tissue microarray (TMA) approach. Material and Methods We studied the immunohistochemical expression and overexpression of EpCAM on TMAs containing formalin‐fixed, paraffin‐embedded samples of 948 patients with documented renal tumours. EpCAM expression was defined as the presence of a specific membranous staining in >5% of the tumour cells. EpCAM overexpression was specified by calculating a total staining score (score range 0–12) as the product of a proportion score and an intensity score, and defined as a score >4. Results Of 948 cases, 927 (97.8%) were evaluable morphologically (haematoxylin and eosin stain). EpCAM expression was found in 233/642 (36.3%), 126/155 (81.3%), 54/68 (78.3%), 17/45 (37.8%), 13/30 (43.3%) of clear‐cell RCC, papillary RCC (pRCC), chromophobe RCC (cpRCC), oncocytomas and other unclassified tumour types, respectively. Log‐rank tests showed a significantly longer overall survival (OS [P = 0.047]) and a trend of EpCAM expression to be associated with a longer progression‐free survival (PFS) in all RCC entities (P = 0.065). EpCAM overexpression was significantly correlated with a better PFS in all RCC subtypes, cpRCC and pRCC (P = 0.011, 0.043 and 0.025, respectively). In multivariate analysis EpCAM overexpression was an independent marker for longer PFS in all RCC entities as well as in high grade RCC (P = 0.009 and P = 0.010, respectively). Conclusions The histological subtypes associated with a high rate of EpCAM expression were cpRCC and pRCC. This retrospective analysis demonstrated a trend towards longer OS and PFS for all major RCC subtypes. EpCAM expression had significant prognostic value in patients with cpRCC and pRCC. Furthermore, EpCAM overexpression in high grade RCC may be a helpful marker for prognostication.